ECOLOGICAL ICMS IN GOIÁS: APPLICABILITY IN INTEGRAL PROTECTION UNITS (CIPEEX, 2023)
The present work presents the 'State of the Art' scheduled for the preparation of a Master's Thesis being developed in the stricto sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda records the importance of studies focused on investigating the environmental practices scheduled and implemented by the municipalities of Goiás that are covered by the Monetary Participation Index (IPM) from the Ecological ICMS, which are directed towards the protection, promotion, and preservation of the Integral Protection Units (UPI) present on the borders of the State of Goiás. To achieve success, a deductive approach was employed, enhanced by bibliographic and documentary techniques, which allowed the development of research of a descriptive and explanatory nature.
Keywords: Brazil; Ecological ICMS; Integral Protection Units